Valeur maximale de surtravail en RD. Congo - BAISOMBI BWANYE Eugène; LILEMBAMYFATHER; MOSONGO BOFANDO Charles (IJRDO - Journal of Applied Management Science, 2020)
The maximal value of under work in the operating system to work is the work of several thinkers us touch Karl Marx in his different works. The exploitation, under exploitation, work, under work, deserves the exo thus on work, the exo on exploitation to observe the human dignity. This different concepts place to this research is the philosophical inspirations that we think of it, to think to meditate or even to put an end out of work and to poverty. So therefore, in a nation as ours, the under work is of a big carried to win the overproduction of goods it by the conquest of the power of the state. Work is an inescapable value that we note his/her/its disappearance within our enterprises (societies of transformation). Being a strength, the states that is authorized work should assume its responsibilities in all these shapes for so to maximize the returns. This State must legislate the rules or the laws to hold to a good work; these rules or laws are considered like BALISEURS of work.